Isolation and molecular identification of Rhizoctonia solani and Fusarium solani isolated from cucumber (Cucumis sativus L.) and their control feasibility by Pseudomonas fluorescens and Bacillus subtilis - Fadhal A. Al-Fadhal; Aqeel N. AL-Abedy; Duaa A. Alkhafije (Egyptian Journal of Biological Pest Control, 2019)
Abstract This study was conducted to isolate and molecularly identify two pathogenic fungi namely Rhizoctonia solani and Fusarium solani implicated in root rot and seedling damping-off disease of cucumber, Cucumis sativus. Besides, the efficacy of Pseudomonas fluorescens and Bacillus subtilis as bacterial agents in controlling these two pathogens was also evaluated in vitro and in a greenhouse pot experiment. Results of polymerase chain reaction (PCR) amplification and nucleotide sequence analysis using BLAST demonstrated that R. solani isolate was genetically different from the R. solani isolates in the National Centre for Biotechnology Information (NCBI). Therefore, it was recorded in GenBank under the accession number MK105921. P. fluorescens and B. subtilis showed a complete inhibition of the mycelial growths of R. solani and F. solani in vitro. In the pot experiments, soil treatment with a suspension of P. fluorescens and B. subtilis before planting significantly reduced the damping off of cucumber seedlings caused by R. solani and F. solani. This study suggests that these bacterial antagonists could have a good potential as biological control agents to protect cucumber plants from the infection with R. solani and F. solani.